Heat depletion in sedimentary basins and its effect on the design and electric power output of CO2 Plume Geothermal (CPG) systems. (July 2021) - Adams, Benjamin M.; Vogler, Daniel; Kuehn, Thomas H.; Bielicki, Jeffrey M.; Garapati, Nagasree; Saar, Martin O.
Abstract: CO2 Plume Geothermal (CPG) energy systems circulate geologically stored CO2 to extract geothermal heat from naturally permeable sedimentary basins. CPG systems can generate more electricity than brine systems in geologic reservoirs with moderate temperature and permeability. Here, we numerically simulate the temperature depletion of a sedimentary basin and find the corresponding CPG electricity generation variation over time. We find that for a given reservoir depth, temperature, thickness, permeability, and well configuration, an optimal well spacing provides the largest average electric generation over the reservoir lifetime. If wells are spaced closer than optimal, higher peak electricity is generated, but the reservoir heat depletes more quickly. If wells are spaced greater than optimal, reservoirs maintain heat longer but have higher resistance to flow and thus lower peak electricity is generated. Additionally, spacing the wells 10% greater than optimal affects electricity generation less than spacing wells 10% closer than optimal. Our simulations also show that for a 300 m thick reservoir, a 707 m well spacing provides consistent electricity over 50 years, whereas a 300 m well spacing yields large heat and electricity reductions over time. Finally, increasing injection or production well pipe diameters does not necessarily increase average electric generation. Highlights: CO₂ Plume Geothermal (CPG) power is simulated as the reservoir state changes. Correctly sized well spacing will provide the greatest average power over time. Over-spacing wells affects the average power less than under-spacing them. Optimum well spacing increases as permeability increases. Maximizing the well pipe diameter may not produce the most heat or power over time.